Ensuring the resilience of Ukrainian education during the war as an experience for improving the education systems in the EU countries - Londar, Sergiy; Bosenko, Oleksandr; Gaiduk, Ivan (My University, 2024)
The resilience of an educational system during wartime is determined by its capacity for rapid adaptive response to exogenous threats, internal structural reconfiguration, and the preservation of equitable access to high-quality education for all stakeholders. Ensuring systemic resilience requires not only legislative and regulatory modifications but also the integration of advanced technological solutions, the implementation of innovative governance frameworks, and the reengineering of the educational ecosystem to sustain operational continuity. This study seeks to identify, critically analyse, and systematically categorise the principal managerial strategies, technological interventions, and policy frameworks that have reinforced the adaptive capacity of Ukraine's education system under wartime conditions. The study further explores the scalability of these resilience-enhancing mechanisms within the context of European Union (EU) educational infrastructures. The analysis concerns key administrative and pedagogical reforms enshrined within legislative and regulatory instruments that have facilitated the systemic stabilisation and operational resilience of Ukraine's education sector. Particular emphasis is placed on the evolution and institutionalisation of digital learning infrastructures, which have become integral to the functional continuity of the educational process at all levels. The study evaluates the deployment of digital information management systems, AI-driven educational analytics, cloud-based e-learning platforms, and dynamic decision-support dashboards developed by the Ministry of Education and Science of Ukraine. These digital tools have significantly optimised real-time communication channels, facilitated comprehensive situational monitoring, and enabled data-informed policy formulation within the sector. Furthermore, they have played a pivotal role in the large-scale implementation of distance learning modalities, the preservation and dissemination of Ukrainian-language instructional content for displaced learners, and the adoption of innovative, evidence-based pedagogical methodologies. The study conducts a rigorous assessment of the empirical outcomes of these strategic interventions, with a focus on their implications for educational achievement metrics, institutional stability, and the psychological resilience of students and educators. Additionally, the research systematically identifies and synthesises the resilience deficits within EU educational frameworks, particularly in response to crisis-induced disruptions. The compounded impact of the COVID-19 pandemic and the unprecedented influx of refugee students from Syria, Ukraine, and various African regions have exposed critical vulnerabilities in the EU’s educational infrastructure, necessitating comprehensive structural recalibration. Ukraine's extensive experiential knowledge in maintaining educational continuity amidst severe sociopolitical upheaval presents a valuable repository of best practices. This accumulated expertise offers actionable insights for the European academic community, facilitating the development of robust contingency frameworks capable of sustaining inclusive, high-quality education in the face of systemic volatility. Стійкість системи освіти в умовах війни визначається її здатністю швидко реагувати на зовнішні загрози, внутрішньо трансформуватися, адаптуватися до змін та забезпечувати доступ до якісного навчання для всіх учасників освітнього процесу. Це вимагає не лише законодавчих і нормативних змін, а й інноваційних технологій, нових підходів до управління та організації освітнього середовища. Метою статті є ідентифікація, вивчення й систематизація основних управлінських рішень, технологічних змін і стратегій, що забезпечили стійкість системи освіти України в умовах війни, задля їх можливого масштабування в інших країнах, зокрема державах-членах ЄС. У статті розглядаються ключові управлінські рішення, закріплені законодавчими та нормативно-правовими актами, освітянські підходи, які сприяли підвищенню стійкості української освітньої системи. Особливу увагу приділено аналізу розвитку інформаційних технологій, що на сьогодні вже застосовуються на всіх стадіях і рівнях української освіти та стали важливою складовою забезпечення її стійкості. Зокрема, розглянуто управлінські й навчальні технології з використанням інформаційних систем, електронних платформ, оперативних інформаційних дашбордів МОН, які стали важливими інструментами розвитку комунікацій, моніторингу ситуації та прийняття обґрунтованих рішень у сфері освіти. Їх використання також забезпечило впровадження дистанційного навчання, функціонування програм зі збереження україномовного контенту для дітей-біженців та реалізацію інших інноваційних педагогічних підходів. Проаналізовано результати цих рішень, а також їх вплив на якість освіти й психічний стан учнів і вчителів. Окрім того, ідентифіковано та узагальнено виклики стійкості в системах освіти країн ЄС. Пандемія COVID-19 і наплив упродовж останніх років школярів-біженців із Сирії, України, країн Африки виявили в освіті ЄС цілу низку недоліків, які потрібно виправляти. Система освіти України має цінний досвід виживання у складних обставинах, сформовано величезну базу знань, що може бути використана європейською спільнотою для організації навчання в турбулентних соціальних умовах із метою забезпечення доступу до шкільної освіти для всіх дітей і підтримання її належної якості.
Keywords: war; digital technologies; EU education systems; система освіти; війна; цифрові технології; освітні системи ЄС; освітні системи ЄС